Modernization of technological tools for crop monitoring and water use efficiency in LAC agriculture - Balbontín, Claudio; Bavestrello, Claudia; Calera, Alfonso; Garrido, Jesús; García, Claudio; Otero, Álvaro; Martinez, Roberto Simon; Gonzalez Aubone, Fernando; Puertas, Carlos Marcelo; Montenegro, Ayelen; Rios, Liliana; Wallberg, Britt; et al. (SPIE, 2024)
Trabajo presentado a: Remote Sensing for Agriculture, Ecosystems, and Hydrology XXVI, 16 - 19 September 2024, en Menteith, Escocia. Financiado por: FONTAGRO Proyecto Plataforma de gestión del agua en la agricultura 2030, ATN_RF-17950-RG